1996
DOI: 10.22358/jafs/69602/1996
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of faba bean hulls for ruminants

Abstract: Faba bean hulls fed at the rate of 18.3% DM of the diet decreased crude protein digestibility (P<0.01) and increased N-retention (3.8 g vs 5.5 g) in growing sheep. Significantly higher glucose level and decreased urea content in blood serum has been found within experimental animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The same could be observed for other animal species such as sheep [125] and pigs [126,127]. In a group of sheep fed with husks, at least a slight increase in the nitrogen retention could be proven [125]. Rubio et al [128] have not been able to find any effect from the inclusion of husks or autoclaved husks in the feed of broiler chickens compared to husk-free feed.…”
Section: Husks-feed Usementioning
confidence: 65%
See 2 more Smart Citations
“…The same could be observed for other animal species such as sheep [125] and pigs [126,127]. In a group of sheep fed with husks, at least a slight increase in the nitrogen retention could be proven [125]. Rubio et al [128] have not been able to find any effect from the inclusion of husks or autoclaved husks in the feed of broiler chickens compared to husk-free feed.…”
Section: Husks-feed Usementioning
confidence: 65%
“…In growing broiler chickens, it was shown that the addition of tannins to the basic feed significantly reduced protein digestibility and that this effect increased with increasing tannin content [151,152]. The same could be observed for other animal species such as sheep [125] and pigs [126,127]. In a group of sheep fed with husks, at least a slight increase in the nitrogen retention could be proven [125].…”
Section: Husks-feed Usementioning
confidence: 66%
See 1 more Smart Citation
“…In addition, the use of whole plant faba bean silage as a forage source has been tested and the potential was proved (McKnight and MacLeod 1977). However, the study to test the nutritional value of faba bean partitions is limited, only one study has been conducted by Minakowski et al (1996) about faba bean hulls and suggested that the inclusion rate should not exceed 20% of the diet.…”
Section: Introductionmentioning
confidence: 99%